Outcomes of Definitive Treatment of Signet Ring Cell Carcinoma of the Rectum: Is Minimal Invasive Surgery Detrimental in Signet Ring Rectal Cancers? - Raghavan, S. (Indian J Surg Oncol, 2020)
The outcome of surgery for signet ring adenocarcinoma of rectum is suboptimal with high predilection for locoregional and peritoneal metastases. Lack of intercellular adhesion due to focal loss of epithelial cell adhesion molecule (EpCAM) may account for this. In such patients, whether minimal invasive surgery carries a high risk of dissemination by pneumoperitoneum and tumor implantation remains uncertain. The aim of this study was to compare the outcomes of patients undergoing minimally invasive surgery (MIS) versus open surgery in patients with signet ring cell adenocarcinoma of rectum. A retrospective study was conducted at a tertiary care center over 3 years on 39 patients undergoing open surgery and 40 patients undergoing MIS diagnosed with signet ring cell carcinoma (SRCC) identified from our surgical database. Patient characteristics in terms of demographics, clinicoradiological staging, neoadjuvant therapy, and type of surgery with morbidity were compared in the two groups. Data on patients undergoing adjuvant therapy and 3 years disease-free survival (DFS) and overall survival (OS) were analyzed. Recurrence patterns in both groups were separately identified as locoregional, peritoneal, or systemic. The number of patients undergoing surgery in the two arms was 40 (MIS) and 39 (open). In the MIS arm, mean DFS was 29 months whereas in the open arm, it was 25.8 months. The mean OS was 33.65 months for the MIS arm and that for the open arm was 36.34 months. This retrospective study reveals no significant difference in outcomes of surgery for signet ring cell rectal cancers with either MIS or open approach.